A Brief Study of Google Apps: Exploring the Benefits and Control of Google Apps in Cloud Computing (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Google has been pushing the technological limits of cloud computing for over ten years. Since data in Google Apps is stored in the cloud rather than on employee computers, various users can access and add to ventures at the same time without agonizing over utilizing the same operating system, software, or program. Moving to Google's cloud doesn't mean you lose control of your data or your technology. The Google Apps Terms of Service unequivocally express that clients hold responsibility for data in Google Apps, and Google solidly trusts the clients ought to have the capacity to effectively get their data out of Google Apps on the off chance that they ever choose to quit utilizing the service. Besides, Google Apps gives controls so chairmen can oversee which applications their users can access and how employees can utilize each service. At long last, Google Apps APIs permits managers construct custom usefulness and mixes with different advancements.